2013
DOI: 10.2478/acph-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and application of a molecularly imprinted polymer for determination of glibenclamide residues

Abstract: The performance of a molecularly imprinted polymer (MIP) as selective packing material for solid-phase extraction (SPE) of residual glibenclamide in an industrial process was investigated. MIP was prepared using 4-vinylpyridine as monomer, ethylenedimethacrylate as cross linker, 2,2’-azobis-2-methylpropionitrile as initiator and dimethyl formamide as porogen. Use of acetonitrile as a rebinding solvent allows good recognition of the glibenclamide template. It was found that this polymer can be used for determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Glibenclamide (GB) or glyburide (5‐chloro‐ N ‐[2‐[4[(cyclohexylamino)carbonyl]amino]sulfonyl]phenyl]ethyl]‐2‐methoxy benzamide) (Figure ) is known as a common drug for the treatment type 2 diabetes . It can be quickly absorbed from the digestive system and act as a powerful and long‐term antidiabetic agent . GB is related to the second generation of sulfonylureas and can perform the antidiabetic role via increasing the release of internal insulin from pancreas beta cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glibenclamide (GB) or glyburide (5‐chloro‐ N ‐[2‐[4[(cyclohexylamino)carbonyl]amino]sulfonyl]phenyl]ethyl]‐2‐methoxy benzamide) (Figure ) is known as a common drug for the treatment type 2 diabetes . It can be quickly absorbed from the digestive system and act as a powerful and long‐term antidiabetic agent . GB is related to the second generation of sulfonylureas and can perform the antidiabetic role via increasing the release of internal insulin from pancreas beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey showed that the detection of GB in pharmaceuticals and biological liquids has been commonly based on the high‐performance liquid chromatography (HPLC) techniques with various detection systems, such as UV, fluorescence or mass spectrometry . These methods are tedious, time‐consuming, high‐priced, difficult and need a skilled operator .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, many studies have focused on developing bionic antibodies. Molecularly imprinted polymer (MIP) has many complementary cavities to the template molecule in shape, size, and chemical function, making them specific and selective to the target molecule [15][16][17]. During the past decades, the increasing trend of imprinting biologically active compounds ranging from small pharmaceutical molecules to large biomacromolecules including myoglobin, naproxen, antioxidants, diclofenac and urea has been numerously reported [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the noncovalent approach is experimentally more straight forward relative to the covalent printing method because the stage of its complexity is achieved only by mixing the template with functional monomers in the appropriate solvent. Such did not require template derivatization, and template removal is usually sufficient by washing polymers [21]. One of the most reliable modern analytical methods is liquid chromatography tandem-mass spectrometry (LC-MS), which has advantages of both accurate identification and quantification of analyte target.…”
Section: Introductionmentioning
confidence: 99%